2008
DOI: 10.1088/0953-4075/41/19/195203
|View full text |Cite
|
Sign up to set email alerts
|

Single-electron capture in keV Ar15+…18++He collisions

Abstract: Single-electron capture in 14 keV q−1 Ar15+…18++He collisions is investigated both experimentally and theoretically. Partial cross sections and projectile scattering angle dependencies have been deduced from the target ion recoil momenta measured by the COLTRIMS technique. The comparison with close-coupling results obtained from a two-centre extension of the basis generator method yields good overall agreement, demonstrating the applicability of close-coupling calculations to collision systems involving highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
(23 reference statements)
2
16
0
Order By: Relevance
“…tfischer@mpi-hd.mpg.de and yields very good overall agreement with the experimental partial as well as DCSs [7]. So far, BGM calculations for highly charged projectile ions up to q = 20 are available.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…tfischer@mpi-hd.mpg.de and yields very good overall agreement with the experimental partial as well as DCSs [7]. So far, BGM calculations for highly charged projectile ions up to q = 20 are available.…”
Section: Introductionsupporting
confidence: 58%
“…[13]. Although we have not made such a comparison here, Knoop et al [7] showed that a TC-BGM calculation can give a good agreement with the experimental state-selective angular distribution.…”
Section: A Single-electron Capturementioning
confidence: 77%
See 2 more Smart Citations
“…Especially at higher impact energies E p > 100 keV/u, where the final electronic state determination in experiments is challenging or often impossible, the influence of excitation has not been investigated [20][21][22][23]. Projectile scattering angle distributions, which are final state selective, are rather rare [1,24,[26][27][28][29][30][31][32]. All these measurements were only possible due to the development of a modern momentum imaging technique, cold target recoil ion momentum spectroscopy (COLTRIMS) combined with optimized threedimensional focusing ion optics, which achieves longitudinal momentum resolution <0.04 a.u.…”
Section: Introductionmentioning
confidence: 99%